Enhancing energy harvesting performance of a flat plate solar collector through integrated carbon-based and metal-based nanofluids - Nuhash, Mashrur Muntasir (2024)
Flat Plate Solar Collectors (FPSCs) have been widely employed in the production of renewable energy for a significant period. To enhance their thermal performance, the utilization of nanofluids as heat transfer fluids has emerged as a popular approach. However, many research works were only carried out with conventional metal-based nanofluids. This numerical study investigates the effects of incorporating two carbon nanotubes, namely single-walled carbon nanotube (SWCNT)/water and multi-walled carbon nanotube (MWCNT)/water, on the fluidic and thermal performance of FPSC. The Nusselt (Nu) and Stanton (St) numbers, as well as the frictional characteristics, are measured and compared to those of metal-based nanofluid of alumina (Al2O3)/water at volume concentrations up to 1%. It is found that Nu increases with a higher Reynolds number (Re) while deteriorating at a higher volume concentration. The lowest Nu was recorded for SWCNT/water in the current investigation. The Stanton number increases with a higher volume concentration and decreases with an increase of Re. Notably, the maximum value of 0.001801 is obtained for the SWCNT nanofluid. The outlet temperature decreases maximum for SWCNT/water with the increase of Re and volume concentration while the friction factor decreases with increasing Re and is independent of the type of nanofluids. Maximum thermo-hydraulic performance parameter of 1.48, 1.32 and 1.29 is achieved for SWCNT, Al2O3 and MWCNT, respectively.